The association between apelin gene polymorphism and coronary artery disease in young patients with acute obstructive coronary syndrome - Ramazan Güven; Kamil Can Akyol; Nermin Bayar; Mustafa Keşaplı; Muhammed İkbal Şaşmaz; Asım Arı; Şakir Arslan (KARE Publishing, 2017)
Objective: The purpose of this study was to evaluate the association between V103V, 6140AG, TGA-Stop-TAA Stop, and 6016CA polymorphisms of the apelin (APLN) gene detected for the first time among young patients with acute coronary syndrome (ACS) and coronary artery disease (CAD). Methods: This was a prospective cross-sectional study. The study population was divided into 2 groups. The first group included 132 patients who were found to have critical lesions in their coronary arteries, while the control group consisted of 41 patients who were found to have normal coronary arteries or non-critical atherosclerotic lesions. Results: Among the gene polymorphisms, V103V was found to be more common in the critical CAD patients with the GG genotype compared with the control group (67.4% vs. 46.3%). On the other hand, the GT genotype was more common in the control group (53.7% vs. 32.6%). Univariate and multivariate logistic regression analysis revealed that the GG genotype of V103V was an independent predictor for the presence of critical CAD (odds ratio: 2.397; 95% confidence interval, 1.174-4.892; p=0.016). Conclusion: In cases of V103V polymorphism of the APLN gene, patients with the GG genotype were at a greater risk for the presence of atherosclerotic critical lesions compared with the control group.